Symbolic computations in modern education of applied sciences and engineering - Kamiński, Marcin (Computer Assisted Methods in Engineering and Science, 2008)
A presentation of the modern issues related to the symbolic computing is contained here together with the detailed discussion of its application to the education of various scientific and engineering academic disciplines. The future expansion of the symbolic environment is described here on the basis of their historical and modern developments presentation. As it is shown on the example of the MAPLE system, symbolic computational environments play the very important role in supporting the lectures and the classes in the computer labs. Those environments may be also very useful in teaching basic natural sciences in all those cases, when some algebraic or differential equations appear, must be solved and their results should be precisely discussed. The application of the MAPLE and similar computer systems in the engineering education seems to be unquestionable now and some examples are contained here to show how to improve the lectures and make them very interesting and exciting. The key feature offered by the symbolic computing is the opportunity to discover the knowledge that the students may do by themselves, when they are specifically leaded by the instructors.